From Superman to Superior Man : Anthropology of Perfection in Traditional Cosmology - Amir H. Zekrgoo (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2011)
It is obvious that the use of these various terms does not result in a miscellany of ideas such as it occurs in many New Age theories. In perennialists’ writings we have come to realize that this is not an attempt to mix traditions together, but is instead an attempt to utilize existing terminology when it is appropriate. The paper has focused at studying the anthropology of perfection in perennial philosophy. It has addressed issues such as the nature of  ‘self  and the states of self-realization’, selfessness and selﬁ shness’, ‘the categories of  man’, ‘the process of  exaltation’, ‘attributes’, ‘qualities’, ‘rights and obligations of the superior man in traditional worldview. In various places of  the paper we have resorted to artworks belonging to various traditions and different times to communicate the ideas and worldviews. They show how essential the role of artists and the art they produce is in keeping alive the reverence for perfection and continuity of  tradition through their inspired imagination. The superior qualities are not necessarily those of rulers and conquerors. They are rather to be found in mythical heroes, prophets of  God and sages of various traditions; those who, in Ghazali’s words, “possess inner vision”. Such individuals hold attributes of perfection; their bodies die, yet their characters live beyond time and space inspiring generations after generations. After all, to be a superior being means starting a never-ending journey of  becoming.